How to think like da Vinci - Smith, Daniel (New York Michael O'Mara Books Limited, 2015)
"Gathering together the philosophies and analysing the carefully honed skills of history's most talented individual, this inspiration book invites you to explore Leonardo Da Vinci's unique approach to creatitity, art and science. Tracing disparate ideas and influences that helped shape him, it will reveal how you can apply his methods to all areas of your life. You, too, can learn to think Leonardo, history's greaest polymath."
This edition is published by MJF Books in arrangement with Michael O"Mara Books Limited."
Includes bibliographical references (pages 187-188).
Keywords: Leonardo, da Vinci -- 1452-1519.; Creative thinking